Criteria-based management of an acute multistructure knee injury in a professional football player: A case reporübersetzter Titel (DE) - Yenchak, A. J.; Wilk, K. E.; Arrigo, C. A.; Simpson, C. D.; Andrews, J. R. (Journal of Orthopaedic & Sports Physical Therapy, 2011)
STUDY DESIGN: Case report. BACKGROUND: Joint stiffness, also called arthrofibrosis, remains the primary complication following any reconstructive knee surgery. Acute anterior cruciate ligament surgery, performed with concomitant multiple ligamentous repair and/or reconstruction, further increases the likelihood of developing impaired knee motion following surgery. The purpose of this case report is to present a criteria-based approach to the postoperative management of a multiligament knee injury. CASE DESCRIPTION: A 25-year-old male professional football player sustained a contact injury to his right knee while making a tackle during a regular season game in 2007. He underwent an acute anterior cruciate ligament reconstruction, with concomitant posterolateral corner repair, biceps femoris/iliotibial band repair, lateral collateral ligament repair, and a medial meniscocapsular junction repair. He completed 17 weeks of a multiphased rehabilitation program that emphasized immediate range of motion, low-load long-duration stretching, therapeutic exercise, neuromuscular reeducation/perturbation training, plyometrics, and sport-specific functional drills. Electrical neurostimulation was implemented during the early stages of rehabilitation to control postoperative pain and to promote a steady progression of therapeutic exercise activity. OUTCOMES: The patient was cleared to begin sport-specific activity 7 months after major multistructure reconstructive knee surgery. He began the 2008 season on the physically-unable-to-perform list, but was activated midseason and played in every game thereafter. During the 2009 and 2010 seasons, he played all regular season games and all playoff games as a starter, and continues to start as a defensive cornerback in the National Football League. DISCUSSION: This case report highlights the clinical decision-making process and management involved in an acute multiple ligamentous knee injury/reconstruction. LEVEL OF EVIDENCE: Therapy, level 4.